Capitalizing on the Placebo Component of Treatments. Issue 4 (July 2015) - Beedie, Chris; Foad, Abby; Hurst, Philip
<x xml:space="preserve">Abstract</x> A placebo treatment is traditionally administered in a double-blind randomized controlled trial to control for the "real" effects of the treatment under investigation. In the present article, a broader view of the placebo is proposed, one in which the idea of a potentially "useable" placebo component of a sports or exercise medicine treatment is presented. It is argued that many interventions in sport and exercise psychology might contain a placebo component that could be capitalized upon by practitioners through processes often as simple as communicating positive expectations from a treatment to clients. Research findings relating to factors that might influence an individual's response to a placebo, such as personality, situation, and genetics, are briefly addressed. Ethical considerations for practice and future research are discussed.